民间歌谣《月光光》研究 ：口语特点与文化内涵 = A study of the Chinese folk songs corpus entitled Yue Guang Guang : oral features and cultural implication - 张嘉嘉 Teo, Jia Jia (2016)
现今，越高级的娱乐休闲往往伴随越昂贵的价格，换句话说休闲娱乐是靠金钱消费来换取的。然而在古早时期，民间歌谣是其中一种人人都能参与的普遍娱乐。歌者依照自己的喜好和记忆，自由地创编歌谣，因此产生了不同版本的民间歌谣《月光光》。为了突出民间歌谣《月光光》的内容特色，本文以内容的类型分类文本，并探讨文本所蕴含的传统文化。 此外，本文依据《月光光》的起首程式，将文本归类为 “月光光，秀才X”、“月光光，照XX”、“月X月光光”、“月光光，好种X”以及“月光光，XXX”(“X”为可变动的词或词组)，并运用“帕里—洛德”口头程式理论来分析《月光光》文本中的“口语特点”，以探究文本的创编、记忆与传播的问题。 多数的民间歌谣《月光光》是儿歌，歌词多以农村的事物与传统文化为题材，也不乏逗趣的内容。有些儿歌《月光光》的歌词中甚至提及生殖器以及身体部位。这些被认为“粗俗”的歌词是研究民间文学的重要线索。因为文本反映了儿童对游戏的喜好、知识水平以及价值观等。本文参考赫伊津哈（Johan Huizinga）的“游戏理论”，分析歌谣《月光光》的游戏成分，也探讨文化语境的转变如何影响儿歌“月光光”的式微。 对歌者来说 ，演唱儿歌《月光光》是对观众承担展示自己交流能力的责任，因此歌者的创编和表演，是为了获得听众的青睐和认同。而听众欣赏《月光光》的表演时会调动曾看过的表演的经验与当下的表演做比较，对表演进行品评。为了符合现代的语境和审美趣味，儿歌《月光光》的创编者应节日、场地和观众等因素，选择了适合在公开场合表演的《月光光》文本或对文本进行改编。本文参考美国著名民俗学家，理查德·鲍曼（Richard Bauman）对口头文学表演的分析与观察，探讨民间歌谣《月光光》表演文本中的变形、特殊的符码、修辞、句法、程式和传统文化等。 In this 21st-century urban life, the more luxurious the entertainment is, the higher the consequential price is. In other words, such entertainment is only obtainable on monetary basis. More often than not, in trying to seek quality life, people have failed to notice the simple pleasures around them. In the early times, singing Chinese folk songs entitled ‘Yue Guang Guang’ ―‘The Moon Shines Brightly’ in English, was one of the entertainments which everyone could afford.Those folk songs t were popular and prevailing at that particular period. Due to their liberal and free-style nature, they could be composed or compiled according to singer’s preferences and memories. As a result, there were varied forms of ‘Yue Guang Guang’being widely disseminated in China orally. In order to elaborate the characteristics of ‘Yue Guang Guang’, the texts are categorized according to their content in Chapter 2. In addition, I have applied “Parry-Lord Theory” which is the way of remembering, composing as well as transmitting texts to study the oral features of ‘Yue Guang Guang’. In Chapter 3, ‘Yue Guang Guang’ are classified based on their “first-line formula”. For instance, “月光光，秀才X”,“月光光，照XX”,“月X月光光”、“月光光，好种X”and “月光光，XXX”, in which “X” can be replaced by different words as per the intention of the singer. Most of the Chinese folk songs corpus entitled ‘Yue Guang Guang’are indeed nursery rhymes. Some of these ‘Yue Guang Guang’ nursery rhymes involve the descriptions of the human anatomy and are rendered vulgar. Nevertheless, this element of vulgarity in the lyric serves as a vital clue to research on folk literature. This is because the element of vulgarity manifests children’s fondness for games, their standard of knowledge as well as values. Therefore, Johan Huizinga’s “play-element” has been employed in chapter 4 and it is particularly useful for studying the play features in ‘Yue Guang Guang’ and Chinese traditional culture. Singing ‘Yue Guang Guang’ is also a performance whereby a singer would like to display his communicative competence in order to attract the audience. At the same time, the audience will evaluate the act of expression according to their experiences. Nowadays, commodifications of culture, the change of aesthetic interest and forms of dissemination have led to the change in ‘Yue Guang Guang’ content. Furthermore, the reason for the infusion of tradition into ‘Yue Guang Guang’ is to blend in with the modern context. Hence, Chapter 5 in this paper deals with Richard Bauman’s “performance theory” which aids in the keying of ‘Yue Guang Guang’ performance.